The influence of different core arrangements on magnetic properties of electrical sheets under one-dimensional magnetizing system - Aisyah Hartini, Jahidin; Mahadi, W.N.L.W. (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org